Retinal hyperspectral imaging in the 5xFAD mouse model of Alzheimer’s disease - Jeremiah K. H. Lim (Nature Portfolio, 2021)
Abstract Hyperspectral imaging of the retina has recently been posited as a potentially useful form of spectroscopy of amyloid-beta (Aβ) protein in the eyes of those with Alzheimer’s disease (AD). The concept of using the retina as a biomarker for AD is an attractive one, as current screening tools for AD are either expensive or inaccessible. Recent studies have investigated hyperspectral imaging in Aβ models however these studies have been in younger mice. Here we characterised hyperspectral reflectance profile in 6 to 17 months old 5xFAD mice and compare this to Aβ in isolated preparations. Hyperspectral imaging was conducted across two preparations of Aβ using a custom built bench ophthalmoscope. In the in vitro condition, 1 mg of purified human Aβ42 was solubilised and left to aggregate for 72 h. This soluble/insoluble Aβ mixture was then imaged by suspending the solution at a pipette tip and compared against phosphate buffered saline (PBS) control (n = 10 ROIs / group). In the in vivo condition, a 5xFAD transgenic mouse model was used and retinae were imaged at the age of 6 (n = 9), 12 (n = 9) and 17 months (n = 8) with age matched wildtype littermates as control (n = 12, n = 13, n = 15 respectively). In the vitro condition, hyperspectral imaging of the solution showed greater reflectance compared with vehicle (p < 0.01), with the greatest differences occurring in the short visible spectrum (< 500 nm). In the in vivo preparation, 5xFAD showed greater hyperspectral reflectance at all ages (6, 12, 17 months, p < 0.01). These differences were noted most in the short wavelengths at younger ages, with an additional peak appearing at longer wavelengths (~ 550 nm) with advancing age. This study shows that the presence of Aβ (soluble/insoluble mixture) can increase the hyperspectral reflectance profile in vitro as well as in vivo. Differences were evident in the short wavelength spectrum (< 500 nm) in vitro and were preserved when imaged through the ocular media in the in vivo conditions. With advancing age a second hump around ~ 550 nm became more apparent. Hyperspectral imaging of the retina does not require the use of contrast agents and is a potentially useful and non-invasive biomarker for AD.